Informant-based assessment instruments for dementia in people with intellectual disability: A systematic review and standardised evaluation. (February 2022) - Zeilinger, Elisabeth L.; Zrnic Novakovic, Irina; Komenda, Sophie; Franken, Fabian; Sobisch, Marc; Mayer, Anna-Maria; Neumann, Lennart C.; Loosli, Sandra V.; Hoare, Sarah; Pietschnig, Jakob
Highlights: The comprehensive COSMIN methodology was used to evaluate instruments. We recommend the BPSD-DS, the CS-DS, and the DSQIID for screening purposes. We recommend the CAMDEX-DS for a more thorough assessment of dementia. There are large gaps in evaluation studies of dementia assessment tools. Most instruments lack an evaluation of their content- and structural validity. Abstract: Background: Dementia in people with intellectual disability (ID) is frequent but hard to recognise. Evidence-based recommendations for suitable instruments are lacking. Aims: The present study set out to evaluate informant-based dementia assessment instruments and to provide evidence-based recommendations for instruments most suitable in clinical practice and research. Method and procedures: A systematic review was conducted across ten international electronic databases. The COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN) guidelines, including a risk of bias assessment, was applied to extract information and to evaluate measurement properties and the quality of available evidence. Outcomes and results: In total, 42 studies evaluating 18 informant-based assessment instruments were analysed. For screening purposes, we recommend the Behavioral and Psychological Symptoms of Dementia in Down Syndrome Scale (BPSD-DS), the Cognitive Scale for Down Syndrome (CS-DS), and the Dementia Screening Questionnaire for Individuals with Intellectual Disabilities (DSQIID). For a more thorough dementia assessment, we recommend the Cambridge Examination for Mental Disorders of Older People with Down's Syndrome and Others with Intellectual Disabilities (CAMDEX-DS). Conclusions and implications: Our study informs clinicians and researchers about adequate, well-evaluated dementia assessment instruments for people with ID, and highlights the need for high quality studies, especially regarding content validity.